2020
DOI: 10.2147/cia.s254740
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>FTO</em> Polymorphisms are Associated with Metabolic Dysfunction-Associated Fatty Liver Disease (MAFLD) Susceptibility in the Older Chinese Han Population</p>

Abstract: Background: As fat and obesity play a vital role in the pathophysiology of metabolic dysfunction-associated fatty liver disease (MAFLD), this study aims to investigate the association between the fat mass and obesity-associated gene (FTO) and MAFLD. Methods: Six SNPs (rs6499640, rs1421085, rs8050136, rs3751812, rs9939609 and rs9930506) within FTO were genotyped for 741 MAFLD patients (median age, 69.98; interquartile range, 66.55-75.93) and 825 healthy people (median age, 69.94; interquartile range, 66.39-75.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…However, they had recruited their population following the criteria for NAFLD. Similarly, Gu et al 22 showed that variations in fat mass and obesity-associated genes are associated with a higher risk of MAFLD in their Chinese cohort. However, they also defined MAFLD according to the NAFLD criteria.…”
Section: Genetic Aspects Of Nafld and Mafldmentioning
confidence: 85%
“…However, they had recruited their population following the criteria for NAFLD. Similarly, Gu et al 22 showed that variations in fat mass and obesity-associated genes are associated with a higher risk of MAFLD in their Chinese cohort. However, they also defined MAFLD according to the NAFLD criteria.…”
Section: Genetic Aspects Of Nafld and Mafldmentioning
confidence: 85%
“…Three GWAS studies in the East Asian populations, such as Korean, Chinese, and Japanese, have identified various mutations in the FTO gene (rs9939609, rs17817449, and rs12149832) as the most significant marker of BMI ( 69 , 70 ). In addition to this, six SNPs of the FTO gene (rs6499640, rs1421085, rs8050136, rs3751812, rs9939609, and rs9930506) were mostly associated with obesity ( 71 , 72 ). Besides the polymorphism of FTO found in obesity, it also contributed to many other diseases among various populations.…”
Section: Discussionmentioning
confidence: 94%
“…Also, the fat mass and obesity-associated gene (FTO) were identified to be linked with obesity risk (and probably with NAFLD as well) [ 23 ]. Higher expression of Iroquois homeobox (IRX) genes 3 (IRX3) and 5 (IRX5), which are effectors of the FTO variants, induce the transformation of the brown adipocytes (energy-dissipating) into white adipocytes (energy-storing) [ 24 ].…”
Section: Pathophysiological Processes In Nafldmentioning
confidence: 99%